Isolated Liner Revision for Total Knee Arthroplasty Instability: A Road That Should Remain Less Taken - Tegethoff, Jason D.; Walker-Santiago, Rafael; Ralston, William M.; Keeney, James A. (The Journal of Knee Surgery, 2020)
Isolated polyethylene liner exchange (IPLE) is infrequently selected as a treatment approach for patients with primary total knee arthroplasty (TKA) prosthetic joint instability. Potential advantages of less immediate surgical morbidity, faster recovery, and lower procedural cost need to be measured against reoperation and re-revision risk. Few published studies have directly compared IPLE with combined tibial and femoral component revision to treat patients with primary TKA instability. After obtaining institutional review board (IRB) approval, we performed a retrospective comparison of 20 patients treated with IPLE and 126 patients treated with tibial and femoral component revisions at a single institution between 2011 and 2018. Patient demographic characteristics, medical comorbidities, time to initial revision TKA, and reoperation (90 days, <2 years, and >2 years) were assessed using paired Student's t-test or Fisher's exact test with a p-value <0.01 used to determine significance. Patients undergoing IPLE were more likely to undergo reoperation (60.0 vs. 17.5%, p = 0.001), component revision surgery (45.0 vs. 8.7%, p = 0.002), and component revision within 2 years (30.0 vs. 1.6%, p < 0.0001). Differences in 90-day reoperation (p = 0.14) and revision >2 years (p = 0.19) were not significant. Reoperation for instability (30.0 vs. 4.0%, p < 0.001) and infection (20.0 vs. 1.6%, p < 0.01) were both higher in the IPLE group. IPLE does not provide consistent benefits for patients undergoing TKA revision for instability. Considerations for lower immediate postoperative morbidity and cost need to be carefully measured against long-term consequences of reoperation, delayed component revision, and increased long-term costs of multiple surgical procedures. This is a level III, case–control study.
Keywords: total knee arthroplasty; isolated polyethylene liner exchange; revisions; prosthetic joint instability; infections